PERATAAN LABA DITINJAU DARI CASH HOLDING, PROFITABILITAS DAN UKURAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA: INCOME SMOOTHING: REVIEW FOR CASH HOLDING, PROFITABILIT,Y AND COMPANY SIZE IN MANUFACTURING COMPANY IN INDONESIA - Asri, Fatjhar; Fauziati, Popi (Universitas Riau, 2022)
The purpose of this research is to look into the impact of cash holding, profitability, and business size on income smoothing subject of this study is a manufacturing business listed on the Indonesia Stock Exchange in the products and consumption sub-sector. Purposive sampling was utilized to collect data. data-binarygistic regression is the data analysis strategy used to confirm the hypothesis is correct. The SPSS application is used to process the information. Cash holding2has a substantial2effect on income smoothing, but profitability and company size has no significant effect on income smoothing in manufacturing and consumption sub-sector companies on the Indonesia Stock Exchange, according to the results of hypothesis testing.